Power Quality Optimization in Dual Active Bridge Converters - Abdul Shakoor; Azhar Ul Haq; Taosif Iqbal (IEEE Access, 2023)
The dual active bridge (DAB) converter is widely used in applications such as energy storage systems (ESSs), charging stations, and solid-state transformers. However, input power fluctuations, such as those encountered in photovoltaic systems or fuel cells, may reduce the system’s damping and cause oscillations in the converter’s output voltage. To minimize ripples under various operating conditions, this paper proposes an optimal inductor-assisted disturbance observer-based disturbance rejection control (DOB-DRC) technique. The components of the high-frequency transformer are precisely modeled, including the series inductance, which is optimally placed for maximum power transfer. The DOB-DRC is designed for voltage regulation with minimum ripples and is compared with other control algorithms, such as current predictive control (CPC), output current feedforward control (OCFFC), and virtual direct power control (VDPC). Experimental results demonstrate that the proposed control strategy achieves fast dynamic performance, minimum overshoot, and steady-state error.